A 48-year-old Man with Epigastric Pain and Melena - Chauhan, Narvir Singh (Archives of Academic Emergency Medicine, 2018)
A 48-year-old male patient presented to the emergency department with the complaints of epigastric pain and melena for the past 3 days. The pain was started suddenly and has progressed and after a while, he passed melena stool. He also mentioned some episodes of vomiting that was not bloody. The pain score was about 8/10 (based on verbal quantitative scale) and slightly radiated to back. He loosed his appetite and the pain aggravated by meal. He did not use any drug regularly and had no positive medical history for specific disease or prior hospital admission. The patient was slightly pale and sweaty. His pulse rate was 80/minute and blood pressure was elevated as 180/100 mm Hg. Routine blood tests such as liver enzyme and serum amylase levels were normal. Complete blood cell count showed mild anemia (Haemoglobin =10 g/dl) and leucocytosis (16600/mm3). On physical examination, there were not any positive findings except mild epigastric tenderness without rebound or guarding. Electrocardiography revealed normal sinus rhythm without any pathologic findings. The patient was admitted in surgical ward and plain abdominal computed tomography (CT) scan and abdominal CT angiogram was done. The findings of CT are shown in figures 1A-D.